From Hatred to Compassion: An Interview With Thupten Phelgye - Joanie Eppinga (Journal of Hate Studies, 2009)
Thupten Phelgye was born in Tibet in 1957. He remembers the chaos brought by the Chinese invasion of his country in 1959. After several failed attempts to escape that resulted in their being placed in concentration camps, Phelgyes parents managed to travel with him to India. There Phelgye heard His Holiness the Dalai Lama explicate four lines of a sutra, an experience that changed his life. He became a monk and, after an individual audience with the Dalai Lama at the age of 17, went into isolation for five years. Since rejoining society he has worked hard to better the lot of his people and of animals, encouraging a vegetarian diet. Phelgye founded the Universal Compassion movement and now represents the Dalai Lama in the Tibetan Government-in-Exile. He spoke briefly with our editor about the transcendence of hatred at Gonzaga University on October 15, 2008.